Site fidelity and population parameters of pantropical spotted dolphins in the Eastern Caribbean through photographic identification - Courtin, Baptiste; Millon, Cédric; Feunteun, Aurore; Safi, Morjane; Duporge, Nathalie; Bolaños-Jiménez, Jaime; Barragán-Barrera, Dalia C.; Bouveret, Laurent; de Montgolfier, Benjamin (Frontiers in Marine Science, 2023)
The Agoa protected marine area, located in the French West Indies, eastern Caribbean, holds several cetacean species, of which the pantropical spotted dolphin Stenella attenuata is the most commonly observed. This species is the focus of whale-watching activities off the leeward coasts of Guadeloupe and Martinique, which has allowed the development of a citizen science program to characterize individuals through the collection of photographic data. Here, we conducted a photo-identification study with a sample of 115,705 photos collected between 2014 and 2019, in which 290 marked individuals (179 in Guadeloupe and 111 in Martinique) were identified. Based on an Agglomerative Hierarchical Classification (AHC) analysis, dolphins from each island were separated into two residency clusters. The Catch–Mark–Release (CMR) POPAN statistical model for open populations estimated the pantropical spotted dolphin populations in Guadeloupe and Martinique at 657 (95% CI: 525–821) and 336 (95% CI: 253–446) individuals for frequent users, respectively, while occasional visitors were estimated at 3,063 (95% CI: 2,133–4,398) and 1,443 (95% CI: 1,024–2,033), respectively. The Martinique population tended to use a reduced coastal area and appeared to be smaller and stable, while the Guadeloupe population showed a slight decline in abundance throughout the study period. These results showed that the leeward coasts of Guadeloupe and Martinique are of particular importance for pantropical spotted dolphin populations, highlighting the need for continued monitoring through both scientific and citizen science programs to fill information gaps on this species in the eastern Caribbean.